Assessment of vertical root fractures using three imaging modalities: Cone beam CT, intraoral digital radiography and film - J. Kambungton (2018)
Objectives: The aim of this study was to assess the accuracy of cone beam CT (CBCT) in detecting vertical root fractures and to compare the accuracy with images from an intraoral sensor and from conventional intraoral film. Methods: 60 extracted, single-rooted human teeth were divided equally into two groups: a control group of 30 teeth and an induced fracture group of 30 teeth. All teeth were randomly placed into sockets in six dry mandibles. Each tooth was imaged by three modalities: CBCT, intraoral digital radiography and intraoral F-speed film. Three beam angulations (an orthogonal projection and additional projections with ±20° horizontal shifts of the central ray) were used when radiographs were made using film and a digital sensor. Three oral and maxillofacial radiologists evaluated the presence of root fractures twice in each image modality using a five-point confidence rating scale. Areas under receiver operating characteristic curves (Az) were computed for each observer and modality and were tested for statistical differences using the Kruskal-Wallis test. Results: There was no statistical difference in the performance of the three modalities (mean of Az values: CBCT 5 0.811, film 5 0.797 and sensor 5 0.775; p=0.771). Conclusions: There was no significant difference between intraoral film, a high-resolution complementary metal oxide semiconductor digital imaging system and CBCT in detecting vertical root fractures in mandibular single-rooted teeth. © 2012 The British Institute of Radiology.